2000
DOI: 10.1590/s0104-42302000000100006
|View full text |Cite
|
Sign up to set email alerts
|

Complicações da cateterização arterial em crianças

Abstract: The main complications of this proceeding are related to the technic utilized, time of utilization of the catheter and to the characteristics of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The main complications of arterial puncture are bleeding, bruising, peripheral ischemia and pain. ( 20 - 22 )…”
Section: Discussionmentioning
confidence: 99%
“…The main complications of arterial puncture are bleeding, bruising, peripheral ischemia and pain. ( 20 - 22 )…”
Section: Discussionmentioning
confidence: 99%
“…Some authors demonstrated a low complication rate, with only 3% of catheter occlusion when using a heparin solution continuously, at 3mL/h ( 26 ) . A study performed with adult patients reported no difference in patency of the catheters when comparing maintenance with normal saline at 0.9% and saline solution at 0.9% with heparin, but found differences in the accuracy of the values of blood pressure measurement, and the most accurate values were observed in the group using heparin ( 28 ) . In children from 1 month to 2 years old catheterized in the radial artery and connected to a device with a continuous infusion, at 3mL/h with heparinized isotonic saline at 1IU heparin / mL, there was a higher number of haemorrhage and ischemia in the first 72 hours ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Alguns autores demonstraram baixo índice de complicações, com apenas 3% de oclusão do cateter ao se usar a solução de heparina de forma contínua, a 3mL/hora ( 26 ) . Estudo realizado com pacientes adultos não relatou diferença de permeabilidade dos cateteres ao comparar a manutenção com solução fisiológica normal a 0,9% e solução fisiológica 0,9% com heparina, mas encontrou diferenças quanto à acurácia dos valores da medida da pressão arterial, sendo os mais precisos no grupo que utilizou heparina ( 28 ) . Em crianças entre um mês e dois anos, cateterizadas na artéria radial e conectadas a um dispositivo com fluxo contínuo de infusão a 3mL/hora com solução salina isotônica heparinizada a 1UI heparina/mL, observou-se maior número de hemorragia e isquemia nas primeiras 72 horas ( 29 ) .…”
Section: Discussionunclassified